Comparison of clinical profile and outcomes in patients with carbapenem resistant and carbapenem sensitive gram-negative bacteraemia - Kavuri, Amarnath; Selvaraj, Sethuraj; Raveekumaran, Vignessh; Chenthil, K.S. (Rzeszów University Press, 2025)
Introduction and aim. Carbapenem-resistant Gram-negative bacteraemia (CR-GNB), an emerging public health concern due to limited treatment options and high mortality rates. Carbapenems, face reduced efficacy against resistant strains, posing a significant challenge. The aim was to compare clinical profiles and outcomes between CR-GNB and carbapenem-sensitive (CS-GNB) and to identify factors influencing mortality among these patients. Material and methods. This prospective study was conducted at the tertiary care teaching hospital, enrolling 115 patients with GNB (55 CR-GNB and 60 CS-GNB). Following institutional approval and informed consent, patients underwent standardized testing (blood culture and susceptibility testing) with the VITEK method. Results. CR-GNB patients had significantly longer hospital stays (12.88 vs. 8.87 days, p=0.001), higher ICU admissions (90% vs 49.3%), and prolonged antibiotic use (8.7 vs 6.04 days, p=0.001). Pneumonia was more prevalent in CR-GNB (42.5%) while UTIs dominated in CS-GNB cases (64%). Kaplan-Meier analysis showed increased mortality risk in CR-GNB, with hazard ratios of 1.82 (day-14) and 2.12 (day-28). Conclusion. Thus, in our study CR-GNB posed a significant hazard for mortality risk. Thus, early identification, stringent infection control measures, and antimicrobial stewardship are crucial and to develop effective treatment strategies tailored to high-risk populations can enhance patient survival and limit the resistance.
The Institutional Ethical Committee (MGMCRI/Res/01/2021/38/IHEC/78) approved this study.
Keywords: antimicrobial stewardship; beta-lactam antibiotics; arbapenem; gram-negative bacteraemia